Synthesis of zeolitic imidazolate framework-8 (ZIF-8) using different solvents for 2 lead and cadmium adsorption - Ahmad, Siti Zu Nurain; Wan Salleh, Wan Norharyati; Yusof, Norhaniza; Mohd Yusop, Mohd Zamri; Hamdan, Rafidah; Ismail, Ahmad Fauzi (2023)
The current study is focused on the facile synthesis of zeolitic imidazolate framework-8 (ZIF-8) at room temperature 14 using three different solvents: ammonia solution (ZIF-8 (N)), aqueous solution (ZIF-8 (H)), and methanol (ZIF-8 (M)). 15 The ZIF-8s produced have high crystallinity with different sizes and shapes. The morphology of ZIF-8 (H) resembled 16 the mixture of cubic and the rhombic dodecahedron with truncated corners, whereas ZIF-8(M) occurred as the most 17 stable rhombic dodecahedron, and ZIF-8(N) appeared as cubes with truncated corners. ZIF-8 (N) had the largest 18 average particle size of 573 nm, followed by ZIF-8 (H) and ZIF-8 (M) with average sizes of 108 nm and 62 nm, 19 respectively. ZIF-8 (N) showed a rapid Pb(II) and Cd(II) adsorption, within 15 min, while ZIF-8(H) achieved Pb(II) 20 and Cd(II) equilibrium within 240 min, and 300 min for ZIF-8 (M). The adsorption of Pb(II) and Cd(II) is best fitted 21 with the Langmuir isotherm and pseudo-second-order kinetic model. The maximum adsorption capacities for Pb(II) 22 and Cd(II) sorption were 454.55 and 312.50 mg/g for ZIF-8 (H), 434.78 and 277.78 mg/g for ZIF-8 (M), respectively, 23 and 476.19 and 263.16 mg/g for ZIF-8 (N), respectively. All of the prepared ZIF-8s showed a promising competency 24 as adsorbents for the removal of Pb(II) and Cd(II) from an aqueous solution.